2021
DOI: 10.1096/fj.202101397r
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin protects against liver and vascular damage in a model of diet induced steatohepatitis by resetting FXR and GPBAR1 signaling

Abstract: Farnesoid‐x‐receptor (FXR) agonists, currently trialed in patients with non‐alcoholic steatosis (NAFLD), worsen the pro‐atherogenic lipid profile and might require a comedication with statin. Here we report that mice feed a high fat/high cholesterol diet (HFD) are protected from developing a pro‐atherogenic lipid profile because their ability to dispose cholesterol through bile acids. This protective mechanism is mediated by suppression of FXR signaling in the liver by muricholic acids (MCAs) generated in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 99 publications
(200 reference statements)
0
23
0
Order By: Relevance
“…Since these human data demonstrated that either the leukotrienes pathway or GPBAR1 were upregulated in patients with NAFLD, we have decided to explore whether their modulation is beneficial in a model of NAFLD/NASH. We and others have previously reported that feeding mice a diet enriched in lipid and cholesterol and fructose in the drinking water (HFD-F) to simulate the high caloric intake caused by Western diet, leads to the development of liver injury showing the prototypical changes, steatosis, steatohepatitis, and fibrosis, detected at histopathology analysis in NASH patients ( Carino et al, 2017a ; Carino et al, 2019a ; Carino et al, 2019b ; Marchianò et al, 2022 ). In this experimental setting, HFD-F feed mice were treated orally with compound 2, 30 mg/kg for 54 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these human data demonstrated that either the leukotrienes pathway or GPBAR1 were upregulated in patients with NAFLD, we have decided to explore whether their modulation is beneficial in a model of NAFLD/NASH. We and others have previously reported that feeding mice a diet enriched in lipid and cholesterol and fructose in the drinking water (HFD-F) to simulate the high caloric intake caused by Western diet, leads to the development of liver injury showing the prototypical changes, steatosis, steatohepatitis, and fibrosis, detected at histopathology analysis in NASH patients ( Carino et al, 2017a ; Carino et al, 2019a ; Carino et al, 2019b ; Marchianò et al, 2022 ). In this experimental setting, HFD-F feed mice were treated orally with compound 2, 30 mg/kg for 54 days.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of Cyp7a1 in this model of NAFLD ( Fiorucci et al, 2021 ) is of relevance, since CYP7A1 is the rate-limiting enzyme in the synthesis of primary bile acids in the liver ( Chiang and Ferrell 2020 ). We have recently shown that mice react to an HFD-F by increasing the rate of conversion of cholesterol into bile acids ( Marchianò et al, 2022 ), and that this mechanism allows us to increase the fecal excretion of cholesterol, a protective mechanism that might contribute to limit liver fat accumulation in mice. Despite that regulation of CYP7A1 is different in human and mice ( Fiorucci et al, 2021 ), there is robust evidence that CYP7A1 activation is protective against liver cholesterol accumulation (steatosis), inflammation, and fibrosis ( Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In colon carcinogenesis, cholesterol metabolism and bile acid signaling were closely coordinated [ 43 , 44 ]. As an inhibitor of HMG-CoA reductase, statin also influenced the bile acid pool via FXR modulation [ 23 , 45 ]. In the aspect of angiogenesis, statin was found to induce endothelial apoptosis and angiostatic effect through geranylated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Statins act on transcriptional regulation by interfering with nuclear hormone receptors such as FXR [ 22 ]. The protective effect of atorvastatin in mice on a high-fat diet was discovered to be due to the drug’s ability to reset FXR signaling [ 23 ]. Additionally, atorvastatin regulates the enterohepatic circulation of BAs by inhibiting FXR mRNA and protein expression [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the regulatory effects bile acids exert on lipid and glucose homeostasis in various tissues, several steroidal and non-steroidal ligands of FXR/GPBAR1 have been developed for the treatment of NASH 12 . However, while some of the agents have been advanced though clinical studies, several side effects have been observed, the most common of which are pruritus that typically occurs with obeticholic acid 24 in dose/dependent manner, along with the worsening of lipid lipoprotein profile toward a more proatherogenic lipid profile 25 , 26 . Obeticholic acid has also been associated to a cluster of hepatic decompensation in cirrhotic patients 27 .…”
Section: Introductionmentioning
confidence: 99%